If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5s + -5) + -10 = -2(7s + 5) + -2 Reorder the terms: -2(-5 + 5s) + -10 = -2(7s + 5) + -2 (-5 * -2 + 5s * -2) + -10 = -2(7s + 5) + -2 (10 + -10s) + -10 = -2(7s + 5) + -2 Reorder the terms: 10 + -10 + -10s = -2(7s + 5) + -2 Combine like terms: 10 + -10 = 0 0 + -10s = -2(7s + 5) + -2 -10s = -2(7s + 5) + -2 Reorder the terms: -10s = -2(5 + 7s) + -2 -10s = (5 * -2 + 7s * -2) + -2 -10s = (-10 + -14s) + -2 Reorder the terms: -10s = -10 + -2 + -14s Combine like terms: -10 + -2 = -12 -10s = -12 + -14s Solving -10s = -12 + -14s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '14s' to each side of the equation. -10s + 14s = -12 + -14s + 14s Combine like terms: -10s + 14s = 4s 4s = -12 + -14s + 14s Combine like terms: -14s + 14s = 0 4s = -12 + 0 4s = -12 Divide each side by '4'. s = -3 Simplifying s = -3
| y-4=7x+x^2 | | 2x^2-24x-14=0 | | 5q^2+20pq=0 | | 144-25n^2= | | x^2=1225 | | 121x^4-81y^6=0 | | 17=4x+3-3x | | -2x+43=-23 | | 8x+16=3x+84 | | 4(m+4)=2(6M+8) | | 3p-13p=60 | | x^2+20pq=0 | | x^2+x+1=-.5 | | 12s=-5 | | 5T+7=14-9 | | n^2-49= | | 4x+3+27=0 | | (2a^2-5b)(2a^2+5b)= | | 4t^3-12t+5t^6-15t^4=0 | | (P+16)+(3P-31)+P=980 | | 3x^2-16x+5= | | (4a+b)(4a-b)= | | 4x+1=-1x-11 | | (7r+4)(3r-9)=0 | | (a^2-6)(a^2+6)= | | k^2-17k-60=0 | | 3x+7y=4 | | 57263857638746x(57438754x+5x+5743x)=58325698475387568(5x-54376) | | (7a-1)(7a+1)= | | 12y=11(y+6) | | 10+x=2x | | 49z^2-70z+25=0 |